2019
DOI: 10.1039/c9sc01447k
|View full text |Cite
|
Sign up to set email alerts
|

Salting-in species induced self-assembly of stable MOFs

Abstract: A general strategy based on the Hoffmeister effect is proposed for the aqueous-phase and mild synthesis of stable metal–organic frameworks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 44 publications
0
43
0
Order By: Relevance
“…Our ongoing research demonstrated that Hofmeister ions had an important effect on the growth process of MOFs. [10] A series of salting-in ions can facilitate the crystallization of MOFs through a unique solubilization-mediating mechanism so that many stable MOFs could be obtained in aqueous phase and mild conditions, which are compatible for the self-assembly of soft templates. These early studies strongly inspired us to develop a rational polymeric surfactant self-assembly strategy to obtain ordered large-pore mesoMOFs with excellent chemical stability based on the Hofmeister effect.…”
mentioning
confidence: 99%
“…Our ongoing research demonstrated that Hofmeister ions had an important effect on the growth process of MOFs. [10] A series of salting-in ions can facilitate the crystallization of MOFs through a unique solubilization-mediating mechanism so that many stable MOFs could be obtained in aqueous phase and mild conditions, which are compatible for the self-assembly of soft templates. These early studies strongly inspired us to develop a rational polymeric surfactant self-assembly strategy to obtain ordered large-pore mesoMOFs with excellent chemical stability based on the Hofmeister effect.…”
mentioning
confidence: 99%
“…À ions would attract and bridge Ce nodes to the BDC ligands (mediating). [10] The local concentration of the MOF precursors would increase by the mediation of ClO 4 À ions, which promoted the growth of the crystallized MOFs around the Ce-PEO complexes coronas (Step 2). The experimental scenarios agree with our proposal that no mesoporous structure could be obtained in the absence of ClO 4…”
Section: Zuschriftenmentioning
confidence: 99%
“…Fortunately, the Hofmeister effect, first noted in 1888, provides us a new perspective for overcoming these inherent limitations. Our ongoing research demonstrated that Hofmeister ions had an important effect on the growth process of MOFs . A series of salting‐in ions can facilitate the crystallization of MOFs through a unique solubilization‐mediating mechanism so that many stable MOFs could be obtained in aqueous phase and mild conditions, which are compatible for the self‐assembly of soft templates.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations